SISTEM PRE PROJECT SELLING DALAM PENJUALAN SATUAN UNIT APARTEMEN MENURUT UNDANG -UNDANG NOMOR 20 TAHUN 2011 TENTANG RUMAH SUSUN (CONTOH KASUS PUTUSAN PENGADILAN NEGRI JAKARTA PUSAT NOMOR: 616/PDT.G/2017/PN.JKT.PST JO. PUTUSAN PENGADILAN TINGGI JAKARTA NOMOR: 20/PDT.G/2019/PT.DKI) - Mika Anabelle; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2019)
Pre-Project Selling is a marketing and apartment sales activity conducted before construction is carried out, which is often done by developers before licensing is issued specified in Law Number 20 of 2011 concerning Flats so often causes problems. The purpose of this paper is to determine the pre-project selling system in the sale of apartment units according to the Law on Flats and legal protection for buyers of apartments with a pre-project selling system if the developer defaults.The research method used in this study is a normative research method. The research data was collected by means of a literature study using the method of approaching the law relating to this study, namely Law Number 20 of 2011 concerning Flats.The results of this study show that the sales system with this pre-project selling system often creates problems because the requirements as stipulated in the apartment laws have not been fulfilled, therefore developers can be held accountable both civil, criminal and administrative.